2019
DOI: 10.1186/s40798-019-0182-3
|View full text |Cite
|
Sign up to set email alerts
|

Verifying Head Impacts Recorded by a Wearable Sensor using Video Footage in Rugby League: a Preliminary Study

Abstract: BackgroundRugby league is a full-contact collision sport with an inherent risk of concussion. Wearable instrumented technology was used to observe and characterize the level of exposure to head impacts during game play.PurposeTo verify the impacts recorded by the x-patch™ with video analysis.Study designObservational case series.MethodsThe x-patch™ was used on eight men’s semi-professional rugby league players during the 2016 Newcastle Rugby League competition (five forwards and three backs). Game day footage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 61 publications
0
26
0
Order By: Relevance
“…One rugby study that included six concussions used the X-Patch to determine the number of head impacts that occurred but did not report the magnitude of the head acceleration. 32 The accuracy of the X-Patch has been investigated and the linear acceleration was found to be in reasonable agreement with a reference sensor but the angular acceleration was underestimated by up to 25%. 33 Sim-G is a headband sensor developed by Triax Ltd. A validation study of this sensor found that due to the movement of the sensors relative to the skull, PLA errors could be up to 370%.…”
Section: Introductionmentioning
confidence: 93%
“…One rugby study that included six concussions used the X-Patch to determine the number of head impacts that occurred but did not report the magnitude of the head acceleration. 32 The accuracy of the X-Patch has been investigated and the linear acceleration was found to be in reasonable agreement with a reference sensor but the angular acceleration was underestimated by up to 25%. 33 Sim-G is a headband sensor developed by Triax Ltd. A validation study of this sensor found that due to the movement of the sensors relative to the skull, PLA errors could be up to 370%.…”
Section: Introductionmentioning
confidence: 93%
“…Measurement methods fall primarily into two categories: (1) video analysis and (2) the analysis of time series data acquired by inertial sensors such as accelerometers and gyroscopes [6,11,16,19]. In the former, orthogonal xyz spatial components of well-defined fiducial markers are tracked through a time-series sequence of video frames.…”
Section: Introductionmentioning
confidence: 99%
“…In the former, orthogonal xyz spatial components of well-defined fiducial markers are tracked through a time-series sequence of video frames. This information can then be numerically processed to estimate the dynamics of the markers over the measurement period [19]. In the latter, the orthogonal xyz components of linear acceleration and rotational velocity are measured by the inertial sensors.…”
Section: Introductionmentioning
confidence: 99%
“…The former often come in the shape of inertial measurement units (IMUs). Since these IMUs gather data for a single point in space the placement of the IMU is critical for the measurement [ 17 , 19 , 20 , 21 , 22 ]. Depending on the application the IMU may be placed directly on the skin [ 17 ] a wristband, harness or similar [ 23 , 24 ], but also within a ball, shoe or alike is common [ 25 ].…”
Section: Introductionmentioning
confidence: 99%